Pneumococcal septic arthritis after splenectomy in Felty's syndrome. Issue 10 (October 1991) - Brzeski, M; Smart, L; Baird, D; Jackson, R; Sturrock, R
Abstract : A patient with Felty's syndrome who developed bilateral knee septic arthritis and septicaemia due to Streptococcus pneumoniae is described. She had had a previous splenectomy for symptomatic thrombocytopenia, having received pneumococcal vaccine before the operation. Measurement of antibody to the 23 vaccine serotypes showed protective concentrations before infection to just two. The infecting serotype was not represented in the vaccine, but a vigorous antibody response to this serotype occurred. The patient also developed glomerulonephritis due to immune complex deposition.